The Allied Health Expansion Program: Rethinking how to prepare a workforce to enable improved public health outcomes - Dalton, Lisa M.; Hills, Andrew P.; Jayasinghe, Sisitha; Strong, Kendra; Hyland, Paula; Byrne, Nuala M. (Frontiers in Public Health, 2023)
Improvements in global public health require universal health care supported by a health workforce with competencies appropriate for local population needs–the right capabilities, in the right place, and at the right time. Health inequities persist in Tasmania, and Australia more broadly, most notably for those people living in rural and remote areas. The article describes the curriculum design thinking approach being used to codesign and develop a connected system of education and training to target intergenerational change in the allied health (AH) workforce capacity in Tasmania, and beyond. A curriculum design thinking process is engaging AH participant groups (faculty, AH professionals, and leaders across health, education, aged and disability sectors) in a series of focus groups and workshops. The design process deals with four questions: What is? What if? What wows? and What works? It also involves Discover, Define, Develop and Deliver phases that continue to inform the development of the new suite of AH education programs. The British Design Council's Double Diamond model is used to organize and interpret stakeholder input. During the initial design thinking discover phase, stakeholders identified four overarching problems: rurality, workforce challenges, graduate skill set shortfalls, and clinical placements and supervision. These problems are described in terms of relevance to the contextual learning environment in which AH education innovation is occurring. The develop phase of design thinking continues to involve working collaboratively with stakeholders to codesign potential solutions. Solutions to date include AH advocacy, a transformative visionary curriculum, and an interprofessional community-based education model. In Tasmania, innovative educational innovations are catalyzing attention and investment in the effective preparation of AH professionals for practice to deliver improved public health outcomes. A suite of AH education that is deeply networked and engaged with Tasmanian communities is being developed to drive transformational public health outcomes. These programs are playing an important role in strengthening the supply of allied health professionals with the right capabilities for metropolitan, regional, rural, and remote Tasmania. They are situated in a broader AH education and training strategy that supports the ongoing development of the AH workforce to better meet the therapy needs of people in Tasmanian communities.